The software architecture role in agile methodologies - Anacleto, Valerio Adrián (2006)
The software architecture role in agile methodologies is not sufficiently documented or formalized by means of a process consistent with the philosophy. The current work’s contributions are: 1) Defining guidelines to implement architecture practices in an agile way and so that they can be applied independently of the development process in use. 2) Setting the grounds for the definition of an agile architecture process.